Design and psychometrics cultural competence questionnaire for health promotion of Iranian nurses - Mehdi Khanbabayi Gol; Abasali Dorosti; Majid Montazer (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: As an important factor in the quality of nursing care, cultural competence of nurses should be assessed to improve the quality of care provided. Nursing care is sensitive to culture; therefore, it is necessary to design a tool for evaluation of cultural competence. In this regard, the present study intended to develop a cultural competence questionnaire for Iranian nurses. MATERIALS AND METHODS: In this methodological study, 350 nurses working in all educational hospitals affiliated to Tabriz University of Medical Sciences were selected through convenience sampling. Questions related to cultural care were selected by experts of this field, and a questionnaire was designed and its validity and reliability were examined. RESULTS: A 20-item questionnaire was developed which assessed the three areas of learning and education, awareness and knowledge, and skills. Cronbach's alpha of the whole questionnaire was 0.912, and its validity based on the Kaiser-Mayer-Olkin Index was 0.891. CONCLUSION: This study provides proper evidence regarding the strength of factor structure and the reliability of the developed questionnaire; therefore, it can be considered as a scientific tool for research, educational, and practical purposes in Iranian nurses.